Implementasi Kebijakan Pojok Konseling Keluarga Pusat Pembelajaran Keluarga di Kelurahan Bubutan - Sunarko, Viandra Rafelia Cahya; Bataha, Katerina (IAI Nasional Laa Roiba Bogor, 2024)
The function of the family is of concern to many parties, one of which is the government's attention because the family is the first step to creating a better quality of life. The aim of establishing a counseling corner is to change behavior or circumstances in clients who previously had or did things that were not good. Another aim is to ensure mental health and find solutions to the problems faced by clients, as well as improving the quality of the client's self. Apart from that, the goal that we really want to achieve with the existence of a counseling corner in the RW hall is to create a better life and personality. So Puspaga services are provided at the Bubutan Village RW Hall, which is one of the innovations of the Surabaya City Government to bring public services closer to the community. Research on Policy Implementation for Family Counseling Corners and Family Learning Centers uses descriptive methods with a case study approach. The results of the research that has been carried out show that the Counseling Corner Facilitators and Puspaga facilitators have been able to provide closer services to the community by providing Puspaga Balai RW services in Bubutan Village which include counseling and psychological assistance, socialization or promotion and parenting services.